2016
DOI: 10.1002/ece3.2527
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally comparing the attractiveness of domestic lights to insects: Do LEDs attract fewer insects than conventional light types?

Abstract: LED lighting is predicted to constitute 70% of the outdoor and residential lighting markets by 2020. While the use of LEDs promotes energy and cost savings relative to traditional lighting technologies, little is known about the effects these broad‐spectrum “white” lights will have on wildlife, human health, animal welfare, and disease transmission. We conducted field experiments to compare the relative attractiveness of four commercially available “domestic” lights, one traditional (tungsten filament) and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 53 publications
(68 reference statements)
4
58
1
Order By: Relevance
“…() recorded more bats of the genus Pipistrellus under white light conditions than under darkness, indicating that species of this genus might hunt opportunistically for insects around white light sources. In our experiment, the relatively high number of feeding buzzes emitted by Nathusius’ bats in the presence of warm‐white LED indicated hunting behavior, even though warm‐white LED light is considered less attractive for insects than cold‐white LED (Eisenbeis & Eick, ; Wakefield, Broyles, Stone, Jones, & Harris, ).…”
Section: Discussionmentioning
confidence: 65%
“…() recorded more bats of the genus Pipistrellus under white light conditions than under darkness, indicating that species of this genus might hunt opportunistically for insects around white light sources. In our experiment, the relatively high number of feeding buzzes emitted by Nathusius’ bats in the presence of warm‐white LED indicated hunting behavior, even though warm‐white LED light is considered less attractive for insects than cold‐white LED (Eisenbeis & Eick, ; Wakefield, Broyles, Stone, Jones, & Harris, ).…”
Section: Discussionmentioning
confidence: 65%
“…The LED light we used was rated as “neutral white” at 4,250 K, slightly “cooler/bluer” than the 4,000 K LEDs used by Pawson and Bader (). Differences in CCTs are unlikely to be the main cause of disparity here as abundances of insects caught at LEDs varying in CCT did not differ from one another statistically (Pawson & Bader, ; Wakefield, Broyles, Stone, Jones, & Harris, ); although see Longcore et al. () concerning LED spectral‐tuning.…”
Section: Discussionmentioning
confidence: 83%
“…Historically, light traps have been used by scientists to survey community composition, monitor beneficial insects (Nabli, Bailey, & Necibi, ), and control insect pest populations (e.g., Goretti, Coletti, Veroli, Giulio, & Gaino, ; Pawson, Watt, & Brockerhoff, ; Wallner & Baranchikov, ). The most common insect orders attracted to and captured in light traps are Diptera, Coleoptera, and Lepidoptera (Mikkola, ; van Grunsven et al, ; Wakefield et al, ). Light‐trapping equipment can differ from ALAN in important ways: Experimental light traps usually emit more short wavelengths, are often without glass shields (which filter UV), and are placed near the ground (Degen et al, ).…”
Section: Attractionmentioning
confidence: 99%
“…Among the common positively phototactic insects, moths (Frank, 1988(Frank, , 2006MacGregor, Pocock, Fox, & Evans, 2015) and aquatic insects (Perkin, Hölker, & Tockner, 2014;Yoon, Kim, Kim, Jo, & Bae, 2010) are best studied. Comparative surveys have shown that, relative to their calculated visibility, short wavelengths are disproportionately attractive to many insects (Barghini & de Medeiros, 2012;Mikkola, 1972; see also Wakefield et al, 2016 for a discussion of infrared wavelengths). Although most insects can perceive short wavelengths (Briscoe & Chittka, 2001;Kelber & Roth, 2006), certain families of moths are more attracted to them than others (van Langevelde, Ettema, Donners, WallisDeVries, & Groenendijk, 2011;Somers-Yeates et al, 2013, see also Wölfling, Becker, Uhl, Traub, & Fiedler, 2016).…”
Section: Desensitization Below)mentioning
confidence: 99%
See 1 more Smart Citation